Federal Donuts - Solomonov, Michael; Cook, Steven (Restaurateur) (Houghton Mifflin Harcourt, 2017)
Meet the five partners behind Federal Donuts and Rooster Soup Co. In their (maybe) true story you'll learn about their origin, their first Donut Robot, and even their FedNuts workout. Oh, and you'll get recipes for their donuts. And their fried chicken. And maybe have a few laughs.